Evaluation of time availability of the selected rescue service of a large city. A case study of Warsaw - Sitek Katarzyna; Pokojski Wojciech; Gołębiowska Izabela (Polish Cartographical Review, 2020)
This article presents the GIS analysis of time availability of the Voivodship Emergency Ambulance and Sanitary Transport Station operates an Independent Public Health Care Facility “Meditrans” in Warsaw. The research focuses on determining the level of service for residents in each district with the emergency service station. In addition, an attempt was made to improve accessibility on the example of three selected districts. The authors attempt to select methodology of planning the location of the emergency service station in order to optimize the level of service for residents.